Protection of Hippocampal CA1 Neurons Against Ischemia/Reperfusion Injury by Exercise Preconditioning via Modulation of Bax/ Bcl-2 Ratio and Prevention of Caspase-3 Activation - Nahid Aboutaleb; Nabi Shamsaei; Hamid Rajabi; Mehdi Khaksari; Sohaila Erfani; Farnaz Nikbakht; Pezhman Motamedi; Ali Shahbazi (Basic and Clinical Neuroscience, 2016)
Introduction: Ischemia leads to loss of neurons by apoptosis in specific brain regions, especially in the hippocampus. The purpose of this study was investigating the effects of exercise preconditioning on expression of Bax, Bcl-2, and caspase-3 proteins in hippocampal CA1 neurons after induction of cerebral ischemia. Methods: Male rats weighing 260-300 g were randomly allocated into three groups (sham, exercise, and ischemia). The rats in exercise group were trained to run on a treadmill 5 days a week for 4 weeks. Ischemia was induced by the occlusion of both common carotid arteries (CCAs) for 20 min. Levels of expression of Bax, Bcl-2, and caspase-3 proteins in CA1 area of hippocampus were determined by immunohistochemical staining . Results: The number of active caspase-3-positive neurons in CA1 area were significantly increased in ischemia group, compared to sham-operated group (P<0.001), and exercise preconditioning significantly reduced the ischemia/reperfusion-induced caspase-3 activation, compared to the ischemia group (P<0.05). Also, results indicated a significant increase in Bax/Bcl-2 ratio in ischemia group, compared to sham-operated group (P<0.001). Discussion: This study indicated that exercise has a neuroprotective effects against cerebral ischemia when used as preconditioning stimuli.